DEPLETION OF STRATOSPHERIC OZONE RESULTING FROM GLOBAL GASEOUS POLLUTION - LOUW, C.W. (Clean Air Journal, 1986)
The possible depletion of the stratospheric ozone layer has become an issue of international importance. The primary concern is based on the possible inhibition of its functioning as a life protecting ultraviolet shield and the adverse biological and climatological effects that might result from this. There is, however, still considerable scientific uncertainty concerning this issue. It is against this background that an appraisal is given of the current state of knowledge regarding the potential for depletion of stratospheric ozone by global gaseous pollution and the attendant environmental effects. Special reference is made to the SA research effort that will make an important contribution towards understanding the tropospheric/stratospheric processes which play a role in the formation and destruction of ozone.